Supraglacial lake outlines and depth estimation in Northeast Greenland from 2016 to 2022 using a thresholding method and radiative transfer equation - Lutz, Katrina; Hochreuther, Philipp; Braun, Matthias Holger; Neckel, Niklas; Reimann, Nathalie; Humbert, Angelika (PANGAEA, 2024)
This dataset contains two components. The first portion consists of supraglacial lake outlines derived from Sentinel-2 optical imagery over the 2016 to 2022 summer melt seasons. These outlines span a region cover around 82,000 km2 over Nioghalvfjerdsbrae (79N Glacier) and Zachariæ Isstrøm in Northeast Greenland. These outlines were derived using the methodology described in Hochreuther et al., 2021 (https://doi.org/10.3390/rs13020205). This method is based on a red-blue threshold with an integrated shadow-masking algorithm. These masks provide a near-daily time series of supraglacial lake development over these seven years. The second portion of this dataset consists of the volume estimation of each lake throughout the time series using the radiative transfer model developed in Philpot et al., 1987 (https://doi.org/10.1364/AO.26.004123). The volume estimates are based on the green band of Sentinel-2 L1C imagery.
Keywords: Depth; Greenland; Nioghalvfjerdsfjorden Glacier; supraglacial lakes; Zachariæ Isstrøm